CONSCIOUS-COMMUNICATIONAL APPROACH IN TEACHING THE RUSSIAN LANGUAGE (Archive of Conferences, 2022)
The modern stage of development of the methods of teaching the Russian language is characterized by a conscious-communicative approach. It is also called cognitive-communicative. The question arises: can communication, or intercourse, be unconscious? Of course not. The name of the conscious-communicative approach emphasizes its main characteristic: learning to communicate is associated with the conscious knowledge of the system of information about the language, the development of the student's cognitive abilities.